Does Access to Foreign Markets Shape Internal Migration? : Evidence from Brazil - Hering, Laura; Paillacar, Rodrigo (Published by Oxford University Press on behalf of the World Bank, 2017)
This paper investigates how internal migration is affected by Brazil’s increased integration into the world economy.We analyze the impact of regional differences in access to foreign demand on sector-specific bilateral migration rates between the Brazilian states for the years 1995 to 2003. Using international trade data, we compute a foreign market access measure at the sectoral level, which is exogenous to domestic migration. A higher foreign market access is associated with a higher local labor demand and attracts workers via two potential channels: higher wages and new job opportunities. Our results show that both channels play a significant role in internal migration. Further, we find a heterogeneous impact across industries, according to their comparative advantage on the world market. However, the observed impact is driven by the strong reaction of low-educated workers to changes in market access. This finding is consistent with the fact that Brazil is exporting mainly goods that are intensive in unskilled labor.